Impact of functional impairment and cognitive status on perioperative outcomes and costs after radical cystectomy: The role of Barthel Index. (28th December 2022) - Tafuri, Alessandro; Panunzio, Andrea; Gozzo, Alessandra; Ornaghi, Paola Irene; Di Filippo, Giacomo; Mazzucato, Giovanni; Soldano, Antonio; De Maria, Nicola; Cianflone, Francesco; Artibani, Walter; Porcaro, Antonio Benito; Pagliarulo, Vincenzo; et al.
Abstract : Objectives: To investigate the association between Barthel Index (BI), which measures level of patients independence during daily living activities (ADL), and perioperative outcomes in a large cohort of consecutive bladder cancer (BCa) patients, who underwent radical cystectomy (RC) at a tertiary referral center. Methods: We retrospectively evaluated data from clinically nonmetastatic BCa patients treated with RC between 2015 and 2022. For each patient, BI was assessed preoperatively. According to BI score, patients were divided into three groups: ≤60 (total/severe dependency) vs. 65–90 (moderate dependency) vs. 95–100 (slight dependency/independency). Regression analyses tested the association between BI score and major postoperative complications (Clavien–Dindo >2), length of in‐hospital stay (LOHS), 90‐days readmission, and total costs. Results: Overall, 288 patients were included. According to BI score, the patient cohort was distributed as follows: 4% ( n = 11) BI ≤60 vs. 15% ( n = 42) BI 65–90 vs. 81% ( n = 235) BI 95–100. Patients with BI ≤60 had more frequent ureterocutaneostomy performed, shorter operative time, higher rates of postoperative complications, longer LOHS, higher rates of readmission, and were associated with higher total costs, compared to patients with BI 65–90 and 95–100. In multivariable regression models, BI ≤60 remained an independent predictor of increased risk of major postoperative complications (odds ratio: 6.62, p = 0.006), longer LOHS (rate ratio: 1.25, p < 0.001), and higher costs ( β : 2.617, p = 0.038). Conclusions: Total/severe dependency in ADL assessed by BI was associated with higher rates of major postoperative complications, longer hospitalization, and higher costs in BCa patients treated with RC. BI assessment should be considered during patients selection process and counseling before surgery.